Managing photons for quantum information processing. - U'Ren, AB; Mukamel, E; Banaszek, K; Walmsley, I (2003)
We study distinguishing information in the context of photonic quantum interference tailored for practical implementations of quantum information processing schemes. In particular, we consider the character of single-photon states optimized for multiple-source interference experiments and for experiments relying on Bell-state measurement and arrive at specific design criteria for photons produced by parametric down-conversion. Such states can be realistically implemented with available technology. We describe a novel method for characterizing the mode structure of single photons, and demonstrate it in the context of coherent light.